PENGETAHUAN IBU DAN DUKUNGAN KELUARGA BERKONTRIBUSI TERHADAP KEBERHASILAN PEMBERIAN ASI ESKLUSIF - JENI ERLANI; ROHMI FADLI; YULI PERMATA SARI; ARY OKTORA SRI RAHAYU; IKA PERMANASARI (Jurnal Ilmu Keperawatan, 2021)
Optimal growth and development of children can be achieved by exclusive breastfeeding for newborns up to the age of six months. Parental knowledge and family support play an important role in the success of exclusive breastfeeding. The purpose of this study was to know associated Parental knowledge and family support with exclusive breastfeeding in Pangkalan Village, Pucuk Rantau District, Kuantan Singingi Regency. This type of research was quantitative with a cross-sectional approach. The study was conducted from September 2020 to February 2021. The population in this study were all mothers who had babies aged 7-12 months with a total sample of 40 people who were taken by purposive sampling. The results of this study found that the knowledge in the good category was 20 people (50.0%), the majority of family support in the good was 22 people (55.0%), and 62.5% getting exclusive breastfeeding. There is a relationship between knowledge (p-value 0.001), and family support (p-value 0.005) with exclusive breastfeeding in Pangkalan Village, Pucuk Rantau District, Kuantan Singingi Regency. It is recommended that health officers at Pangkalan Puskesmas improve and create conditions that support mothers to breastfeed exclusively by engaging in persuasive communication.